Case Report on Oligohydramnios - Lalhriatpuii1, Manjusha Mahakalkar2 , Manoj Patil3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Oligohydramnios is an extremely rare condition where there is a deficiency of liquor amniiin the amount of less than 200Ml at the time of delivery. Sonographically, it is amaximum vertical pocket ofliquor is < 2 cm or the amniotic fluid index is < 5 cm (less than 5 percentiles) is specified.Patient History: A 23years old ANC & 8months mother was admitted on 11.9.2019 with the complaints ofreduced fetal movements and abdominal discomfort.Past History: Patient has history of blood transfusion 3months back and has history of cervical cerclage at7months of pregnancy.Clinical Findings: Reduced fetal movements, abdominal discomfort, leaking of the amniotic fluid, lowamniotic fluid on ultrasound, low maternal weight gain, pre labor rupture of membranes.Investigations: Ultrasonography (AFI=5cm), Hb% - 9.1gm%, MCV-74, MCH-23.5pico/gm, HCT-28.5%,Total WBC Count – 8000/cu.mm, Lymphocytes- 20%.Surgical Management: Patient does not have any past surgical history.Medical Management: Tab. AFI plus BD, L- Arginitrate sachet 5gm/BD/orally, Tab. iron OD, Tab. CalciumOD.Nursing Management: Assess both maternal and fetal conditions carefully, fetal heart rate and vital signsshould be assessed properly. During labor, an amnio-infusion should be given via intrauterine catheter.Fluid should be administered via amniocentesis before giving birth. The level of amniotic fluid may help byincreasing the amount of oral fluid intake.Conclusion: Patient was admitted to AVBRH and was diagnosed as oligohydramnios and got appropriatetreatment and her condition has improved.